Analisis Pembebanan Statis Komponen Crossbar Clinker Cooler dengan Variasi Beban Horizontal terhadap Lubang Pasak - Akbar, M. William; Arafat, Andril; Sari, Delima Yanti; Abadi, Zainal (Al-DYAS, 2024)
A clinker cooler is a very important piece of equipment in the cement industry because it functions to cool the slag or clinker that comes out of the kiln. In the cement industry, the processed clinker is first heated in a rotary kiln at °C and then lowered to temperature again. Next, the crossbar hammer crusher driven by the drive plate crushes the clinker. Clinker is transferred from the cooler inlet to the cooler outlet by this device. The performance of the main clinker cooler due to small errors can cause the kiln to stop working or disrupt other operations, such as in the mile finish area. In certain cases, cement production was disrupted due to a break in the crossbar component in the clinker cooler using the tested software Ansys Workbench 2020. It is hoped that the data from this simulation can be used as a benchmark between the results of the simulation, it can be used as a benchmark between the results of the best modified design for increasing crossbar durability through statistical loading tests with the FEA method.